Optimasi Rute Distribusi Layanan Vaksin Kabupaten pada Graf Lengkap Berindeks K_8^2 - Jessy Arnelia; Alfi Maulani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Graph is a discrete mathematical representation widely used to model connectivity in various fields. This study discusses the application of Hamiltonian concepts on the complete bipartite graph K_8^2 as a model for vaccine service route planning at the local level (district). The graph K_8^2 represents eight health facilities in a region, where each facility consists of seven service locations and one other supporting facility. The research method includes constructing a complete bipartite graph, identifying vertices and circuits, and tracing Hamiltonian paths to visualize routes that connect each vertex once in a closed journey. The results show that the K_8^2 graph is effective for designing vaccine distribution routes that systematically and efficiently connect all facilities across eight districts. The complete bipartite graph with Hamiltonian properties proves applicable as a model for public service route planning, with potential implementation in optimizing health logistics distribution, facility inspection, and emergency response for vaccination services at the local level.